Molecular dynamics simulation of silicon oxidation enhanced by energetic hydrogen ion irradiation. (25th March 2015) - Mizotani, Kohei; Isobe, Michiro; Fukasawa, Masanaga; Nagahata, Kazunori; Tatsumi, Tetsuya; Hamaguchi, Satoshi
Abstract: Molecular dynamics numerical simulations have been performed to clarify the mechanism of enhanced oxidation in Si during silicon gate etching by HBr/O2 plasmas. Such enhanced oxidation sometimes manifests itself as Si recess during gate etching processes. When a Si substrate is subject to energetic ion bombardment together with a flux of radical species, our study has identified the cause of such enhanced oxidation in Si as enhanced O diffusion arising from the momentum transfer from energetic H atoms to O atoms on the surface or in the subsurface of the Si substrate. No chemical effect such as hydrogenation of Si plays a role for the enhanced oxidation. Simulation results are found to be in good agreement with earlier experimental observations of ion-irradiation-enhanced oxidation obtained by beam experiments.